Derivation and analysis of viscoelastic properties in human liver: impact of frequency on fibrosis and steatosis staging - Nightingale, Kathryn R.; Rouze, Ned C.; Rosenzweig, Stephen J.; Wang, Michael H.; Abdelmalek, Manal F.; Guy, Cynthia D.; Palmeri, Mark L. (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2015)
Commercially-available shear wave imaging systems measure group shear wave speed (SWS) and often report stiffness parameters applying purely elastic material models. Soft tissues, however, are viscoelastic, and higher-order material models are necessary to characterize the dispersion associated with broadband shear waves. In this paper, we describe a robust, model-based algorithm and use a linear dispersion model to perform shear wave dispersion analysis in traditionally difficult-to-image subjects. In a cohort of 135 non-alcoholic fatty liver disease patients, we compare the performance of group SWS with dispersion analysis-derived phase velocity c(200 Hz) and dispersion slope dc/df parameters to stage hepatic fibrosis and steatosis. Area under the ROC curve (AUROC) analysis demonstrates correlation between all parameters [group SWS, c(200 Hz), and, to a lesser extent dc/df ] and fibrosis stage, whereas no correlation was observed between steatosis stage and any of the material parameters. Interestingly, optimal AUROC threshold SWS values separating advanced liver fibrosis (≥F3) from mild-to-moderate fibrosis (≤F2) were shown to be frequency-dependent, and to increase from 1.8 to 3.3 m/s over the 0 to 400 Hz shear wave frequency range.